Urban Adaptation to Climate Change: geographers and wicked problems - Andrew Kirby (Boletín de la Asociación de Geógrafos Españoles)
This paper explores the importance of adaptation to climate change impacts in urban areas. The complexity of existing and likely impacts poses unique challenges to all aspects of society, from state to polity and economy. These in turn pose methodological challenges to academic practice, demanding the integration of macro and micro perspectives and pure and applied research. The paper argues that geographers can make significant contributions to this scholarship.